The Compound Expression of HSP90 and INOS in the Testis of Diabetic Rats as Cellular and Pathologic Adverse Effects of Diabetes - Ali Alsarhan; Kawther Faisal Amawi; Inas Saleh Al-Mazari; Hashem Abu Hurirah; Ahed J. Alkhatib (Analytical Cellular Pathology)
Introduction. Diabetes is increasingly prevalent at global level and associated with various impacts including the male reproductive system. Aims. This research is aimed at investigating the influence of diabetes on the localization and expression of HSP90 and iNOS in the testicular tissue of diabetic rats. Methods. A diabetic model was developed through a single injection of alloxan monohydrate intraperitoneally (purchased from Sigma-Aldrich) 120 mg/kg body weight following fasting for 12 hrs. The experiment involved two groups, the control and diabetic groups with 10 albino rats in each group. Diabetes was considered if glucose concentration was ≥200 mg/dl. The experiment duration was for one month. After the experiment had finished, all rats were terminated and prepared for routine histological and immunohistochemical examination. Results. The results revealed that diabetes caused morphological changes at histological level in testicular tissue. Immunohistochemical examination showed that diabetes significantly upregulated the expression of both HSP90 and iNOS in the testicular tissue of diabetic rats as compared with that of the control group (p<0.001). Conclusion. Diabetes may induce adverse health effects on the male reproduction through upregulation of HSP90 and iNOS in the testicular tissue of diabetic rats.